Програма для інтерпретації результатів вертикального електричного зондування "VEZ-4A" - Коліушко, Д.Г.; Руденко, С.С. (Електротехніка і електромеханіка, 2017)
В роботі було запропоновано алгоритм роботи програми для інтерпретації результатів вертикального електричного зондування ґрунту в рамках діагностики стану заземлювальних пристроїв. Математичний апарат для реалізації алгоритму побудовано на базі методів точкового джерела струму, найменших квадратів, Хука-Дживса та еквівалентування. Наведено огляд та основні функції розробленої програми. В работе был предложен алгоритм работы программы для интерпретации результатов вертикального электрического зондировании грунта в рамках диагностики состояния заземляющих устройств. Математический аппарат для реализации алгоритма построен на базе методов точечного источника тока, наименьших квадратов, Хука-Дживса и эквивалентирования. Приведено описание и основные функции разработанной программы. Purpose. Creating a computer program for interpreting the results of vertical sounding the soil in the form of multilayer model most typical for Ukraine. Methodology. The algorithm of the program is constructed on determination the soil structure with the help of the method of point source current, method of analogy and method of equivalent. The option of automatic interpretation based on Hook-Jeeves method. The program is implemented in the programming language Delphi. Results. The computer program «VEZ-4A» has a possibility of the interactive and automatic interpretation sounding results in the multi-layered geoelectrical model. Originality. In first time the computer program for analyzing and interpreting results of the soil sounding by Wenner configuration was created on the base of the analytical solution for field of current point source located in four-, three- or two-layer structure. In paper the review is presented and basic functions of our program are analyzed. Practical value. The program «VEZ4A» is created and adapted for use in the electromagnetic diagnostics of grounding of existing power plants and substations.